Restoring the riverside in a city: an examination of best practices for port revitalisation - Świerczewska-Pietras, Katarzyna (Bulletin of Geography. Socio-economic Series, 2015)
Rivers have been an important element of urban development for centuries, affecting human life and providing a number of functions connected with commerce, defence, transport, communication and culture. Today's river-city relationship takes on a completely different dimension and is considered through the prism of the beauty which shapes the urban landscape and is a key element in integrating its inhabitants. It affects the city's economic fabric, for instance through increased tourism and investment. Besides, it provides an impetus for the implementation of numerous architectural and urban projects whose task is to integrate its space or, as is often the case, insure the future viability of the riverside, including former port areas. Therefore the aim of this paper is to analyse projects which represent so-called best practice in the restoration of city riverside areas using examples from Western European cities which have experienced the implementation of such projects. The paper presents an analysis of cities selected due to the availability of source materials: Düsseldorf, the largest revitalised area, followed by London and Hamburg, the smallest. It should be emphasised that the author will continue her research on the former port areas, focusing mainly on the German sites